ACCOUNTING EDUCATION IN UKRAINE: TRENDS AND PROSPECTS - Gnatiuk, T.M.; Shkromyda, V.V.; Shkromyda, N.Ya.; Vasyliuk , M.M. (The actual problems of regional economy development, 2021)
The article provides a theoretical justification of the processes that necessitate the transformation of the space in which students of accounting education have the opportunity to acquire all the necessary competencies for a rapid transition from study to work in the chosen specialty. A critical assessment of the state of the domestic system of training of accountants and auditors in formal education institutions, which does not realize all the available potential that can offer professional accounting organizations through the integration into the educational process of the results of non-formal and informal education. It is established that potential employers, both on the part of business and on the part of the public sector of the economy, constantly increase the requirements for graduates of accounting, requiring, immediately upon entering the profession, a wide base of technical knowledge and skills and social skills. The broad content of the concept of accounting education allows to associate it equally with graduates of educational institutions at the levels defined by regulations within formal education, and with professional accountants who receive professional qualifications for certain educational programs or independently acquire certain competencies during life in the process of professional activity. workplace. However, due to the inability of university accounting education, which is filled with permissive practices and bureaucratic regulations, to respond in a timely manner to changes in the accounting profession, some of its applicants lose their professional orientation formed at the time of entering the institution under the influence of social environment. In the modern educational space, the issue of didactics, in terms of improving the methods and organizational forms of education, remains a key task that directly affects the development and promotion of the profession. The system of concepts and ideas about organizational and methodological forms of education is generalized, which is an element of strengthening the methodological support of accounting education by introducing new configurations of interaction with students into the educational process. The proposed forms of work require a functional discourse, taking into account the semiotic approach to solving the list of problematic issues.